The Implementation of Interactive Conceptual Instruction (ICI) to Optimize Scientific Communication Skills Achievements on Impulse and Momentum Concept - Evelina Astra Patriot; Miftahul Jannah (Universitas Muhammadiyah Makassar, 2022)
To face the challenges of the industrial revolution 4.0 and society 5.0, the Indonesian nation must continue to prepare quality future generations through education. Educational institutions are required to realize human resources who have creative thinking, critical thinking and problem solving, communicating, and collaborating called 4C. This study aims to get an overview of the implementation of interactive conceptual instruction with multi-representation to optimize the achievement of students' scientific communication skills on momentum and impulse concepts. Employing a descriptive research design with an observation method, this research was conducted at a senior high school in the 2020/2021 academic year. This study involved 20 students in the tenth grade which were selected by using cluster random sampling technique. The scientific communication skills were reflected in three sub-skills, namely scientific writing, group discussion, and knowledge presentation. The results of the study showed that the average values of student scientific communication skills (SCS) from the first to the fourth meeting are 53.3, 66.1, 89.3, and 97.8, respectively. The average value is the result of the average value of scientific communication skills of all respondents in each session. It can be concluded that the implication of interactive conceptual instruction with multi-representation approach can optimize the achievement of students' scientific communication skills on momentum and impulse concepts.